Risk Factors for Post-stroke Depression: A Meta-analysis - Shi, Yu; Yang, Dongdong; Zeng, Yanyan; Wu, Wen (Frontiers in Aging Neuroscience, 2017)
Background: Stroke not only impacts patients physically but also economically. Post-stroke depression (PSD), as a common complication of stroke, always obstructs the process of stroke rehabilitation. Accordingly, defining the risk factors associated with PSD has extraordinary importance. Although there have been many studies investigating the risk factors for PSD, the results are inconsistent. Objectives: The objectives of this study were to identify the risk factors for PSD by evidence-based medicine. Data sources: A systematic and comprehensive database search was performed of PubMed, Medline, CENTRAL, EMBASE.com, the Cochrane library and Web of Science for Literature, covering publications from January 1, 1998 to November 19, 2016. Study Selection: Studies on risk factors for PSD were identified, according to inclusion and exclusion criteria. The risk of bias tool, described in the Cochrane Handbook version 5.1.0, was used to assess the quality of each study. Meta-analysis was performed using RevMan 5.3 software. Results: Thirty six studies were included for review. A history of mental illness was the highest ranking modifiable risk factor; other risk factors for PSD were female gender, age (<70y), neurotism, family history, severity of stroke, and level of handicap. Social support was a protective factor for PSD. Conclusion: There are many factors that have effects on Post-stroke depression. The severity of stroke is an important factor in the occurrence of PSD. Mental history is a possible predictor of PSD. Prevention of PSD requires social and family participation.